NARRATIVE PERSPECTIVE MEDIATED BY MANNER OF MOTION VERBS - Bodean-Vozian, Olesea (My University, 2016)
There is typological variation in the way languages encode manner as an element of a motion event. Languages like English view it as relevant, and the lexicalization of the variety of ways to move results in a rich class of motion verbs, contrary to other types of languages, like Romanian, which leave the manner element to be encoded by verbids or adverbs (for these reasons some linguists refer to the first type as manner-rich and second type as manner-poor languages). Still, several studies contrasting typologically different languages showed that languages of the latter type are not so poor in manner-of-motion verbs. The question then might rather be: which manner components are more likely to be lexicalized? For research purposes, we distinguish manner in terms of objective elements (medium, speed or intensity) and subjective elements (attitude, intention). The aim of the study is to focus on the manner-of-motion verbs that embed an evaluative or qualitative dimension of motion and to examine the way these verbs encode somebody’s perspective in a narrative. The first question in such a case is whose evaluation or point of view is being represented. The second one is how the subjective point of view (narrative perspective) mediated through manner-of-motion verbs in an English narrative ( The Lord of the Rings, by J.R.R. Tolkien) is translated into Romanian, supposedly a manner-poor or low-manner language.

Existăo variaţie tipologicăîn felul în care limbile codificămodul ca element al unui eveniment de mişcare. Limbile precum engleza îl percep drept unul relevant, iar lexicalizarea gamei de mijloace de redare a mişcării a dat naştere unei clase bogate de verbe de mişcare, contrar altor tipuri de limbi, aşa ca româna, în care elementul ce redămodul este codificat de gerunziu sau adverbe. Din aceasta cauză, unii lingvişti numesc primul tip limbi bogate în verbe de mod (în engl. manner-rich), iar al doilea tip – limbi sărace în verbe de mod (în engl. manner-poor). Totuşi, câteva studii care examineazăcontrastiv diferite limbi au demonstrat că limbile din tipul 2 nu sunt atât de sărace în verbe de mişcare de mod. În acest caz, apare întrebarea: care componente ale mişcării au cele mai mari şanse de a fi lexicalizate? În scopuri de cercetare, facem distincţie între mod în termeni de elemente obiective (mediu, vitezăsau intensitate) şi elemente subiective (atitudine, intenţie). Obiectivul major al studiului prezent este dea aborda verbele de mişcare de mod care înglobează dimensiunea calitativă sau evaluativă a mişcării şi de a examina felul în care aceste verbe codifică perspectiva personajelor în cadrul naraţiunii. Astfel, ceea ce ne preocupă este următoarea întrebare: al cui punct de vedere (sau evaluare) este reprezentat? A doua întrebare pe care ne-o adresăm este: cum se traduce în limba română punctul de vedere subiectiv perspectiva narativă) mediat prin verbele de mişcare de mod din textul narativ englez (Stăpânul Inelelorde J.R.R. Tolkien), pornind de la premisa căromâna este o limbă să racăîn verbe de mişcare de mod?
PERSPECTIVA NARATIVĂ MEDIATĂ DE VERBELE DE MIŞCARE DE MOD
Keywords: narrative; typology; motion events; manner of motion verbs; English; Romanian